Effects of running fatigue on lower extremity symmetry among amateur runners: From a biomechanical perspective - Gao, Zixiang; Fekete, Gusztáv; Baker, Julien S.; Liang, Minjun; Xuan, Rongrong; Gu, Yaodong (Frontiers in Physiology, 2022)
The objective of this study was to reveal the effects of running fatigue on the symmetry of lower limb biomechanical parameters in eighteen male amateur runners. The marker trajectories and ground reaction forces were collected before and after the running-induced fatigue protocol. Symmetry angles (SA) was used to quantify the symmetry of each parameter. Normality tests and Paired sample T-tests were carried out to analyze the bilateral lower limb differences and SA of parameters between pre- and post-fatigue. One-dimensional statistical parameter mapping (SPM_1d) was used to compare parameters with the characteristic of one-dimensional time-varying of lower limbs. After fatigue, the SA of knee extension angles, flexion angle, and hip joint moment increased by 17%, 12%, and 11% separately. In comparison, the flexion angle of the knee angle decreased by 5%. The symmetry of internal rotation of three joints in the horizontal plane increased, while the SA of external rotation of the three joints decreased significantly. These findings provide preliminary evidence that fatigue changes lower limb symmetry in running gait and provide potential evidence for the exploration of lower limb function, athletic performance, running-related injuries, and the research and development of footwear and equipment.